Exploring Prosocial Performance and Gender Differences in Pre-school Children Through Music Activities - Lee, Liza; Bhargavi, Vasishta; Lin, Hsiao-Fang; Pavitola, Linda (Frontiers in Education, 2022)
Although gender difference in prosociality has been researched so far, only a very few studies examined the effect of musical methods on positive prosocial behavior. In this preliminary examination, we focused on finding the relation between music activities and prosocial behavior with respect to gender in pre-school children in line with Social Cognitive Learning Theory (SCLT). We observed sixteen pre-school children of 4–6 years, and two kids per student-teacher observer for sixteen sessions, each at a span of 45 min one session per week, and data were collected through situational tests and observational methods. Results show that music methods are positively related to mood stability, reciprocity, and interaction with peers. The findings are discussed in terms of spontaneous reciprocity and gender-specific responses to social behavior.